RESPONSE STUDY OF OLIVE SEEDLING TO FOLIAR APPLICATION OF CHELATED ZINC - Jassim Al-Aareji; Raida AL-Hamadany; Muna Al-Hamadany (Mesopotamia Journal of Agriculture)
This study was conducted during 2005 growing season. Olive seedling of three cultivars (Khodeiri, Dremalali and Sorani), were sprayed with four concentrations of cheated Zinc (0,25,50 and 75 mg Zn.L.-1), two times in the season, one month intervals between each spray, and the first spray is done at the middle of April. Results which were obtained at the beginning of October indicated that there were significant increase in the N,K and Zn concentration in the leaves, seedlings leaves area, stem high and diameter, number of new branches, dry weight of leaves, stem and roots, and a significant decrease in the concentration of P and Fe in the leaves with the increase of Zn concentration in the spray solution. Dremalali cultivars were dominated over Khodeiri and Sorani cultivars in all studied characteristics except, K concentration in the leaves of two cultivars and number of new branches of Khodeiri cultivars. The critical concentration of Zn in the leaves were 55.87 ,58.33 and 44.24 mg. Zn.Kg.-1 for Khodeiri, Dremalali and Sorani cultivars respectively.